High-throughput transcriptomic and proteomic profiling of mesenchymal-amoeboid transition in 3D collagen - Čermák, Vladimír; Gandalovičová, Aneta; Merta, Ladislav; Harant, Karel; Rösel, Daniel; Brábek, Jan (Scientific data, 2020)
The plasticity of cancer cell invasion represents substantial hindrance for effective anti-metastatic therapy. To better understand the cancer cells' plasticity, we performed complex transcriptomic and proteomic profiling of HT1080 fibrosarcoma cells undergoing mesenchymal-amoeboid transition (MAT). As amoeboid migratory phenotype can fully manifest only in 3D conditions, all experiments were performed with 3D collagen-based cultures. Two previously described approaches to induce MAT were used: doxycycline-inducible constitutively active RhoA expression and dasatinib treatment. RNA sequencing was performed with ribo-depleted total RNA. Protein samples were analysed with tandem mass tag (TMT)-based mass spectrometry. The data provide unprecedented insight into transcriptome and proteome changes accompanying MAT in true 3D conditions.
Keywords: sekvenční analýza RNA; proteom; Humans; Tandem Mass Spectrometry; rhoA protein vázající GTP; Neoplasm Invasiveness; lidé; kolagen; Collagen; tandemová hmotnostní spektrometrie; fibrosarkom; pohyb buněk; rhoA GTP-Binding Protein; transkriptom; Cell Movement; nádorové buněčné linie; Transcriptome; Proteome; Fibrosarcoma; invazivní růst nádoru; Cell Line, Tumor; Sequence Analysis, RNA